Information Asymmetry, Lease Incentives, and the Role of Advisors in the Market for Commercial Real Estate - Martijn Dröes; Boris Ziermans; Philip Koppels (Tinbergen Institute, 2017)
Using a unique transactions dataset from the Amsterdam office market, this paper examines the determinants of property lease incentives. The study focuses on the type of landlord involved (institutional/private) and whether the tenant or landlord used an advisor (professional broker) to help negotiate the lease. The results show that an institutional landlord, ceteris paribus, offers 3 percentage points more incentives than a private owner. In addition, a landlord who uses the services of an advisor pays 9 percentage points less incentives. An advisor at the side of the tenant increases incentives by 7 percentage points. However, if both parties use an advisor there are no additional benefits in terms of lease incentives. These findings are in line with a prisoner's dilemma story. Further results show an effect of the lease term and economic cycle on lease incentives. The results in this paper highlight the crucial role of market information, information asymmetry, and bargaining in the market for commercial real estate.
Keywords: R30; D82; L85; 330; commercial real estate; office market; lease incentives; advisor; information asymmetry